A high performance Pb(ii) electrochemical sensor based on spherical CuS nanoparticle anchored g-C3N4. Issue 46 (11th November 2021) - Ning, Jingheng; Wei, Jiaqian; Huang, Shouen; Wang, Faxiang; Luo, Xin; Sun, Chang; Chen, Donger; Wei, Rui; Sha, Liming; Liu, Yongle
Abstract : Highly efficient electrochemical detection of Pb 2+ is achieved by the composite CuS/g-C3 N4, based on a synergistic effect of "coordination/adsorption" on Pb 2+ provided by both g-C3 N4 and CuS. The limit of detection is as low as 4 nM. Abstract : A new electrochemical sensor has been constructed for ultra-sensitive detection of lead ions (Pb 2+ ) by square wave anodic stripping voltammetry (SWASV), based on the copper sulfide/graphitic carbon nitride nanocomposite modified glassy carbon electrode (CuS/g-C3 N4 /GCE). First, spherical CuS nanoparticles with good electrical conductivity were anchored on layered g-C3 N4 with high coordination activity, affording an excellent electrode modifier CuS/g-C3 N4 nanocomposite. Then, the performance of the CuS/g-C3 N4 /GCE and its electrochemical response to Pb 2+ were thoroughly studied, and the sensing mechanism was investigated. On the one hand, the CuS/g-C3 N4 nanocomposite has greatly improved the electron transportation and electrode performance through functional complementarity – CuS endows g-C3 N4 with a good electrical conductivity and a large active specific surface area, while g-C3 N4 endows CuS with high dispersibility and strong adsorption. On the other hand, the CuS/g-C3 N4 modifier has effectively promoted the deposition of trace Pb 2+ from the solution onto the electrode surface by means of synergistic enrichment (crucial for amplification of detection signals) – g-C3 N4 can coordinate with Pb 2+ by its large number of conjugated triazine heterocyclic rings in its molecular framework, while CuS can adsorb Pb 2+ due to its inherent size effect of nanomaterials. The proposed sensor can efficiently detect Pb 2+ in the concentration range of 0.050–5.000 μM with a limit of detection (LOD) as low as 4.00 nM, and can be well applied for the detection of trace Pb 2+ in actual tea samples.